REORIENTASI PERJANJIAN FRANCHISE SEBAGAI UPAYA KESEIMBANGAN HUBUNGAN HUKUM ANTARA PARA PIHAK - Siti Malikhatun Badriah (Faculty of Law, Universitas Diponegoro, 2014)
Reorientation of franchise agreement becomes very urgent, because in the development of society as long as there is an imbalance of legal relationship between frinchisor with franchisee. In addition there is also a deviation from the contract law principles in the either various stages of pre contractual, contractual and post contractual